The Impact of the COVID-19 Pandemic on The Development of Electromobility - Analysis of Changes in Purchasing Preferences - Wojciech LEWICKI; Piotr WRÓBLEWSKI (Communications of International Proceedings, 2021)
Electromobility is an inseparable concept accompanying the considerations about the future of transport, which may redefine its character in the next decade. However, as highlighted in the literature on the subject, one of the key industries that has been severely hit by the COVID-19 pandemic is the automotive industry. Therefore, all plans for the development of electromobility in relation to individual transport were questioned, both on a global and national scale. The aim of the article is an attempt to answer the question of what changes have occurred in the area of ​​purchasing preferences on the demand side in the time of the global crisis. Considering that, as indicated in the literature on the subject, consumer purchasing decisions may play a key role in further plans for the development of electromobility in the current economic situation. The presented research may help answer the question to what extent the COVID-19 pandemic influenced the development of the electromobility disease. The presented results may constitute the basis and incentive for further research in the field of verification of current electromobility development plans in the era of economic stagnation caused by the COVID-19 pandemic.
Keywords: COVID-19; economic crisis; electromobility; market research; automotive industry